Design and Implementation of Sound Synthesizer for Arduino - Richie A.W., ayan; Karna, Nyoman Bogi Aditya; Irawan, Arif Indra (Jurnal Nasional SAINS dan TEKNIK, 2024)
Signal instruments are musical instruments used notonly for music but also to provide signals as a form of auditivecommunication. Along with the development of civilization, signalinstruments are now digitized, and many instruments are poppingup, for example, megaphones, one of which is in the future.Arduino is a micro-controller device often asked to be able tocommunicate with speakers and become a signal instrument thatcan output sound signals. However, because the signal generatedby Arduino is digital, it must be converted into an analog signalfirst by converting the digital signal generated by Arduino intoan analog signal using a DAC circuit. After converting the signalinto a digital signal, it will be forwarded to the amplifier, whichuses a transistor BC337 as a switch to make Arduino a signalinstrument.The system design is based on Arduino nano as a dataprocessing tool, where the data stored in Arduino nano will beforwarded to the DAC circuit and then will be returned to theamplifier before finally being channeled to the speakers toproduce a sound output that matches the data stored on theArduino nano